Pembentukan Kelas Ibu Hamil Sebagai Bentuk Optimalisasi Pemeriksaan Antenatal Care : Pembentukan Kelas Ibu Hamil Sebagai Bentuk Optimalisasi Pemeriksaan Antenatal Care - Suryanti S; Sitti Nurana (Yayasan Ahmad Mansyur Nasirah, 2022)
Maternal mortality rate (MMR) is one indicator that can describe the welfare of society in a country. To obtain accurate information, the government provides a class program for pregnant women to support a comprehensive and sustainable increase in knowledge of pregnant women. Tellumpoccoe village itself routinely conducts Antenatal Care checks at both the puskesmas and posyandu. However, currently it is not supported by the implementation of classes for pregnant women. The method of activity is carried out through steps including training of midwives and posyandu cadres, socialization of classes for pregnant women and implementation of classes for pregnant women. This activity will be held on December 6-31, 2021. Tellumpoccoe village has 11 pregnant women and 5 posyandu cadres spread over 4 hamlets. Pregnant women in Tellumpoccoe village were recorded as having routine pregnancy check-ups and were provided with a KIA book. Pregnant women class is a study group for pregnant women with gestational age between 20 weeks to 32 weeks with a maximum number of 10 participants per class. In this class, pregnant women will learn together, discuss and share experiences about maternal and child health in a comprehensive and systematic manner. Fiber can be carried out on a scheduled and continuous basis. After the activity was carried out, it was found that the participants had knowledge in the good category (93%). So it can be concluded that participants can accept the material provided. Socialization related to classes for pregnant women can help mothers to have a healthy pregnancy.